Madagascar : Increasing Food Security and Nutrition - Murray, Eileen (World Bank, Washington, DC, 2012)
This article previews the Food Security and Nutrition Project, which is primarily active in two of Madagascar's six provinces. The project has three components: (a) income generating activities to be carried out through: (i) the Fonds d'Intervention pour le Developpement (FID) financing labor intensive works and other income generation activities, and (ii) a food for work program targeted to the urban poor in Greater Antananarivo; (b) nutrition interventions including: (i) a community nutrition program in the provinces of Toliary and Antananarivo working through mothers' groups organized by a community nutrition agent supported by nongovernmental organizations to provide nutrition education, arrange supplemental feeding and refer severe cases of malnutrition to nutrition rehabilitation centers operating under medical supervision, and (ii) a national iodine deficiency disorders control program; and (c) institutional strengthening to support the development and execution of an information, education and communication program and support the development of a national food security strategy for the long term.